Centrally mediated abdominal pain syndromes. (June 2019) - Paine, Peter
Abstract: Centrally mediated abdominal pain and the associated narcotic bowel syndrome are functional bowel disorders that are challenging to manage and associated with significant medical harm, including unnecessary investigations, opioids and surgeries. They are distinguished from more common conditions, such as irritable bowel syndrome, by the near-continuous nature of the pain, irrespective of gastrointestinal physiological functioning. Their pathophysiology is obscure and incompletely understood, but they have features consistent with central sensitization. Long-term opioid use can cause hyperalgesia and dysmotility, leading to a vicious cycle of increasing healthcare use and breakdown in the doctor–patient relationship. Gut–brain neuromodulatory drugs, along with a holistic rehabilitative multidisciplinary approach, patient education and opioid detoxification, can lead to improved outcomes.